2007
DOI: 10.1242/jeb.007054
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of the rigid and hydrostatic skeletons of molting blue crabs, Callinectes sapidus Rathbun

Abstract: SUMMARY Molting in crustaceans involves significant changes in the structure and function of the exoskeleton as the old cuticle is shed and a new one is secreted. The flimsy new cuticle takes several days to harden and during this time crabs rely on a hydrostatic skeletal support system for support and movement. This change from a rigid to a hydrostatic skeletal support mechanism implies correlated changes in the function, and thus mechanical properties, of the cuticle. In particular, it must ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 47 publications
0
23
0
1
Order By: Relevance
“…Mechanical testing shows that the flexural stiffness (composite variable EI) of the postmolt cuticle is four orders of magnitude lower than that of the intermolt cuticle, but the breaking strength (stress at fracture in tension) is the same. Thus, although the postmolt cuticle is unable to bear compressive or bending loads, this thin membrane can support large tensile stresses as is required for hydrostatic skeletal support (Taylor et al, 2007). This alternation between the two categories of skeletal support may be widespread for arthropods.…”
Section: Additional Examplesmentioning
confidence: 99%
“…Mechanical testing shows that the flexural stiffness (composite variable EI) of the postmolt cuticle is four orders of magnitude lower than that of the intermolt cuticle, but the breaking strength (stress at fracture in tension) is the same. Thus, although the postmolt cuticle is unable to bear compressive or bending loads, this thin membrane can support large tensile stresses as is required for hydrostatic skeletal support (Taylor et al, 2007). This alternation between the two categories of skeletal support may be widespread for arthropods.…”
Section: Additional Examplesmentioning
confidence: 99%
“…The merus of the blue crab was tested by Hahn & LaBarbera [11], who loaded these limbs to failure in cantilever bending. Young's modulus and strength of material samples from the merus of this same species were measured in a different study [12], which found values of 318 and 9.9 MPa, respectively. These properties were measured in the transverse direction only; however, there is evidence to suggest that the material is isotropic.…”
Section: Experimental Datamentioning
confidence: 99%
“…The several limb segments distal to the merus can be simplified into one single, rigid segment, assumed fixed where it meets the ground. Using body measurements reported in the literature [11,12], we assumed that the merus had a length of 20 mm, a radius of 4.5 mm, a cross section of 15.25 mm 2 and a second moment of inertia (I value) of 135 mm 4 . The distance from the centre of mass of the body to the proximal joint was estimated as 40 mm, the merus was taken to be inclined at an angle of 458 to the horizontal and the joint angle at the distal end of the merus was taken to be 908 [30].…”
Section: Appendix a Stress Analysis Of The Locust Tibia And Crab Merusmentioning
confidence: 99%
“…molting) (Reaka, 1975). During molting, the cuticle that comprises the exoskeleton undergoes such dramatic changes in structure and mechanical properties, becoming as flimsy as plastic wrap before hardening, that animals must rely on hydrostatic skeletal support (Taylor et al, 2007;Taylor and Kier, 2003;Taylor and Kier, 2006). Newly molted animals cannot strike with their soft raptorial appendages and therefore tend to bluff or flee their cavities when threatened by intruders (Steger and Caldwell, 1983).…”
Section: Role Of the Telson In Ritualized Fightingmentioning
confidence: 99%